Imperfect competition and the modelling of expectations in macroeconomics - Rankin, Neil (2018)
We show that when a model of the macroeconomy is based on imperfect, rather than perfect, competition, this may increase the problem of how to model agents’ expectations. We provide a simple example using an overlapping-generations economy with the potential for unemployment. Under certain assumptions about how consumers migrate between locations between the first and second periods of their lives, this extra issue regarding expectations arises. Imperfect competition may increase agents’ forecasting difficulties because they have to forecast not only future equilibrium prices, but also future out-of-equilibrium prices, and by definition the latter are never actually observed.